Employment contracts, psychological contracts, and worker well-being an international study - Guest, David E.; Isaksson, Kerstin, 1952-; Witte, Hans de. (Oxford : Oxford University Press, 2010)
Temporary employment has become a focus of policy debate theory, and research. This text addresses as its core concern the relationship between temporary employment contracts and worker well-being. Covering seven countries, it sheds new light on the nature and role of the psychological contract.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Temporary employment; Labor contract; Temporary employment -- Psychological aspects; Temporary employees -- Psychology; Quality of work life